PEMANFAATAN YOUTUBE DALAM MENINGKATKAN KOMPETENSI TUTOR BIMBEL EDU PRIVATE - Krisda Lakrisida Meinawati (Comm-Edu (Community Education Journal), 2020)
AbstractThis research aims to improve tutor competence Edu Private Bandung. This competency improvement is carried out through training. The training is carried out with a strategy that is carried out with the planning, implementation, and evaluation stages. Based on the identification of the problem that tutors in Edu Private Bandung tutoring are still not innovative in developing the learning media used. The lack of development of instructional media is caused by the lack of innovative tutors and from the lack of support from the institution. The media used in this training is utilizing social media Youtube. The training shows that tutors actively participate in developing learning media. The benefits of this training are to attract students 'attention so that it is easier to understand the material and attract students' attention in the learning process. The final results in this study the training process can be useful for tutors by developing more learning media, fostering student learning motivation, and making the learning atmosphere more lively. The results of this study can be used as input for tutors in other tutors including in other schools in an effort to improve tutor competence in developing learning media.Abstrak Penelitian ini bertujuan untuk meningkatkan kompetensi tutor bimbel Edu Private Bandung. Peningkatan kompetensi ini dilakukan meelalui pelatihan. Pelatihan dilakukan dengan  strategi yang dilakukan dengan tahap perencanaan, pelaksanaan, dan evaluasi. Berdasarkan identifikasi masalah bahwa tutor di bimbel Edu Private Bandung masih belum inovatif dalam mengembangkan media pembelajaran yang digunakan. Kurangnya pengembangan media pembelajaran disebabkan oleh kurangnya inovatif tutor serta dari kurang support nya dari pihak lembaga. Media yang digunakan dalam pelatihan ini yaitu memanfaatkan media sosial Youtube. Dalam pelatihan menunjukkan bahwa para tutor berpartisipasi aktif untuk mengembangkan media pembelajaran. Manfaat pelatihan ini untuk menarik perhatian siswa agar lebih mudah memahami materi serta menarik perhatian siswa dalam proses pembelajaran. Hasil akhir dalam penelitian ini proses pelatihan dapat bermanfaat bagi tutor yaitu lebih mengembangkan media pembelajaran, menumbuhkan motivasi belajar siswa, serta membuat suasana belajar lebh hidup. Hasil dari penelitian ini dapat dijadikan sebagai bahan masukan bagi tutor di bimbel lainnya termasuk di sekolah-sekolah lainnya sebagai upaya untuk meningkatkan kompetensi tutor dalam mengembangkan media pembelajaran.